Role of type I & type II reactions in DNA damage and activation of Caspase 3 via mitochondrial pathway induced by photosensitized benzophenone. Issue 2 (1st June 2015) - Amar, Saroj Kumar; Goyal, Shruti; Mujtaba, Syed Faiz; Dwivedi, Ashish; Kushwaha, Hari Narayan; Verma, Ankit; Chopra, Deepti; Chaturvedi, Rajnish K.; Ray, Ratan Singh
Graphical abstract